Devastating Impact of Covid-19 on Nursing Education - Sharma, Diksha (Innovational: Journal of Nursing and Healthcare, 2024)
At present, where the whole world is undergoing a severe crisis that was not seen before. Somewhere, the maximum impact of coronavirus disease (COVID-19) was also seen among the education of students. Education has changed dramatically, with the distinctive rise of e-learning, whereby teaching is undertaken remotely and on digital platforms. Worldwide, there are currently more than 1.2 billion children in 186 countries affected by school closures due to the pandemic. The COVID-19 has resulted in schools shut all across the world. Globally, over 1.2 billion children are out of the classroom. More than 1.2 billion students and youth across the planet are or have been affected by school and university closures due to the COVID-19 pandemic; this gap is seen across countries and between income brackets within countries. The unplanned and rapid move to online learning – with no training and little preparation will result in a poor user experience that is unconducive to sustained growth. It created a huge impact on every sphere of human life.